Determinan Kecurangan Laporan Keuangan Melalui Fraud Hexagon pada Perusahaan BUMN yang Terdaftar Di BEI - Putra, Moch. Bryan Mandala; Lutfi, Muhammad Ali; Rahayu, Dwi Puji (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2024)
This research uses the fraud hexagon model to detect potential fraud in annual financial reports in stateowned companies listed on the Indonesian stock exchange for the 2018-2022 period. The aim of the research is to reveal the possibility of potential financial report fraud in state-owned companies listed on the Indonesian stock exchange for the 2018-2022 period. Based on the results of data processing, the value of the coefficient of dilution (McFaddien Rsquaried) is only around 12.50%, so that the variables in this research are only able to provide an influence on this value and the rest is influenced by other variables for the 2018-2022 period. For shareholders, investors and creditors, using this methodology to identify fraudulent corporate financial reporting is very helpful.